Social Marketing as a Strategic Mechanism for Strengthening Educational Social Capital in Indigenous Communities: Evidence from the Dayak Meratus of Indonesia - Haris Fadillah; Nauriatul Muharramah; Alvita Sari; Mochammad Noor Dwicahyo; Makherus Sholeh (Fakultas Tarbiyah dan Keguruan UIN Antasari, 2026)
Educational social capital within families plays a pivotal role in shaping children's academic trajectories, particularly in marginalized indigenous communities; however, limited parental education and constrained interaction patterns have hindered the development of educational support among the Dayak Meratus community in South Kalimantan, Indonesia. This study examines social marketing as a strategic mechanism for strengthening educational social capital in indigenous contexts using a participatory action research design integrated with social marketing strategies, involving eighteen Dayak Meratus parents through focus group discussions, poster-based interventions, and structured home visits. Data were collected using validated pretest and posttest questionnaires measuring parental intentions, attitudes, and subjective norms, complemented by teacher observations of student engagement and academic performance, while program effectiveness was analyzed using nonparametric statistical techniques and effect size interpretation. The findings indicate meaningful improvements in parental intention, attitude, and subjective norms toward supporting children's education, demonstrating the effectiveness of social marketing in enhancing parental engagement and strengthening educational social capital within indigenous families; although student engagement and academic performance showed positive trends, the changes were not yet substantial, suggesting that academic outcomes require longer-term intervention and sustained parental involvement. This study contributes to the literature by integrating social marketing with participatory action research and offers practical insights for promoting educational equity and inclusion in indigenous contexts.